Diversity and new records of desmids (Zygnematophyceae, Charophyta) in Central Kalimantan, Indonesia - Adam, Chaidir; Kenins, Alex; Prabowo, Danang A. (Phytotaxa, 2025)
This study provides a comprehensive report on the occurrence, distribution, ecology, and synoptic account of 56 desmid species from Central Kalimantan, including their relevant taxonomic, ecological, and/or biogeographical notes. The identified species, of which 22 were newly recorded in this study, were distributed into 13 genera, namely: Actinotaenium, Bambusina, Cosmarium, Desmidium, Docidium, Euastridium, Euastrum, Haplotaenium, Micrasterias, Pleurotaenium, Staurastrum, Staurodesmus, and Tetmemorus. The majority of the desmids (23) were cosmopolitan species, whereas (11) consisted of rare and endemic species; highlighting the need for more research in appropriate aquatic ecosystem management practices. Our findings contribute not only as a solid baseline reference for microalgae biodiversity studies in Indonesia, but also provide relevant information for future work that utilise desmid biodiversity for monitoring peat water or other freshwater ecosystems in this region, particularly those experiencing potential threats from anthropogenic stressors.